The Reception of Western Music within Colonial Korea －Focusing on the Actual Situation of Higher Music Education for Koreans - Kim, Jiesun (THE HALLYM JOURNAL OF JAPANESE STUDIES, 2020)
This study considers one aspect of the reception of western music in colonial Korea, focusing on Korea’s first department of music in Ewha Women`s College, as well as analyzing the roles of Korean musicians who studied abroad to music schools in Japan. Graduates of the department of music in Ewha Women`s College and Koreans who studied at Japanese music schools acted as elite musicians, greatly contributing to the development of western music in higher and higher education institutions before and after liberation. For example, today this influence is still felt within the western musical terminology and western music theory that had been introduced by these Koreans who had studied abroad in Japan. Japan’s modernized and musical westernization influenced music schools and books on music theory in Korea and resulted in Korea’s current situation of music theory typically being translated into Korean from Japanese. The Japanese version of western music theory that Japan had already incorporated into their own education system passed through Korean foreign exchange students, as well as Japanese music teachers in Korea, and was directly transmitted to colonial Korea. The resulting influence from this interaction was deep and today the same music terminology is still in circulation. KCI Citation Count: 0